Debt and Fiscal Justice in the Global South: Argentina and Indonesia under IMF and World Bank Intervention - Rizky Bangun Wibisono; Mohammad Aditya Wijaya; Chyntia Dwi Ariani; Muhammad Aidil Faradis (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
This article examines sovereign debt as both an economic mechanism and a political instrument that sustains structural inequalities between the Global North and South. Through a qualitative comparative study of Argentina and Indonesia, and drawing on dependency theory, postcolonial political economy and fiscal justice frameworks, the paper argues that international financial institutions such as the IMF and World Bank constrain fiscal autonomy and policy space in developing countries. In the Indonesian context, domestic elites—including technocrats, oligarchs, and state bureaucrats—play a central role in entrenching project-based debt dependency for political and economic gain. While Argentina serves as a cautionary tale, early signs of resistance emerge through South-South cooperation and BRICS-led alternatives. By integrating structural and actor-centered perspectives, this study contributes to debates on global debt governance and calls for reforms that advance distributive and procedural justice in fiscal policymaking. Keywords: IMF, debt diplomacy, global inequality, fiscal justice.